2021
DOI: 10.1155/2021/9970822
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Subchronic Toxicological Evaluation of the Herbal Product HAD-B1 in Rats

Abstract: This study evaluates acute and subchronic toxicity of a Korean herbal formula HAD-B1 in rat to investigate whether HAD-B1 has potential toxicity to humans. First, the study to assess the acute oral toxicity at dose levels of 0, 500, 1000, and 2000 mg/kg body weight (BW) was performed in male and female SD rats (Crl: CD, specific pathogen-free) (n = 5/group). Based on the result of the acute oral study, 4 weeks’ dose range finding study and 13 weeks’ subchronic study were performed (dose range finding study, DR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The previous study demonstrated the safety of HAD-B1 through the toxicological study of long-term and highdosage use (13 weeks, higher than 2000 mg/kg). [8] In vivo and in vitro studies also showed that HAD-B1 has a potential antitumor effect as a growth inhibitor of solid tumors induced by A549 lung cancer cells without remarkable side effects and inhibited the growth of A549 cisplatin-resistant cells in depends on the concentration. [4,5] According to these results, the antitumor effect of HAD-B1 combined with afatinib on H1975 (L858R/T790M double mutation) lung cancer cells was conducted, and the combined treatment of HAD-B1 with afatinib inhibited the proliferation of H1975 cells in a dose-dependent manner without toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous study demonstrated the safety of HAD-B1 through the toxicological study of long-term and highdosage use (13 weeks, higher than 2000 mg/kg). [8] In vivo and in vitro studies also showed that HAD-B1 has a potential antitumor effect as a growth inhibitor of solid tumors induced by A549 lung cancer cells without remarkable side effects and inhibited the growth of A549 cisplatin-resistant cells in depends on the concentration. [4,5] According to these results, the antitumor effect of HAD-B1 combined with afatinib on H1975 (L858R/T790M double mutation) lung cancer cells was conducted, and the combined treatment of HAD-B1 with afatinib inhibited the proliferation of H1975 cells in a dose-dependent manner without toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In an acute and subchronic toxicological evaluation of HAD-B1 in rats, no target organ was determined, and the no observed adverse effect level was >2000 mg/kg BW. [8] In addition, the most effective dosage of HAD-B1 was determined through comparative experiments. Cell experiments (A549, A549/CR) and animal model experiments (lung cancer Xenograft model) determined the most effective composition and dosage.…”
Section: Introductionmentioning
confidence: 99%
“…The test article HAD-B1 used in this study consists of 4 herbs ( Table 1 ). The 3D HPLC analysis of HAD-B1 showed the representative 6 critical compounds including notoginsenoside R1, cordycepin, ginsenoside Rg1, Rb1, α -boswellic acid, and β -boswellic acid [ 20 ]. HAD-B1 was supplied by KyungbangPharm Inc. (Incheon, South Korea).…”
Section: Methodsmentioning
confidence: 99%
“…Each animal was randomly placed in the test group (T1, T2, T3) and the control group. The dose of HAD-B1 was determined based on the results of the previous 13-week repeated oral administration toxicity test in rats [ 20 ]. No toxicological effects were observed for HAD-B1 up to 2000 mg/kg, thereby determining the no observable adverse effect level (NOAEL) of HAD-B1 to 2000 mg/kg.…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of cancer cases treated with Korean herbal medicine has been widely reported in Korean historical literature. Because of the ease of access to herbal medicine in Korea, taking herbal medicine is a fairly 6 The study on the effects of HAD-B1 on the proliferation of A549 cisplatin-resistant lung cancer cells discovered that the formula inhibited A549CR cell growth in a concentration-dependent manner. 10 Kyunghee University conducted studies on the efficacy and safety of the traditional formula Gamiguibitang with cancer patients who had sleep disturbances, and the results showed that the formula could potentially be used to treat cancer patients' sleep disorders.…”
Section: No Region Institutionsmentioning
confidence: 99%